Foxr1 deletion causes microcephaly and leads to cortical and hippocampal hypoplasia - Waxman, Hannah; Kankkunen, Marcus; Gupta, Arya; Dowgiewicz, Margo; Beffert, Uwe; Ho, Angela (Frontiers in Neuroscience, 2025)
Foxr1 is a member of the evolutionarily conserved forkhead box (Fox) family of transcription factors, characterized by a winged-helix DNA-binding domain. We previously demonstrated that Foxr1 deletion in mice results in severe perinatal lethality, cortical thinning, and ventricular enlargement, indicating its essential role in survival and brain development. Here, we extend these findings by showing that Foxr1 knockout mice develop microcephaly accompanied by cortical and hippocampal hypoplasia at postnatal day 0 (P0). Cortical thinning is primarily driven by a significant reduction in layer 2/3 neurons, linked to impaired generation of later-born neurons. This reduction correlates with decreased proliferation of progenitors (Ki67- and Tbr2-positive cells) at embryonic day 16.5 (E16.5), a critical period for upper-layer neurogenesis. In the hippocampus, Foxr1 knockouts exhibit reduced area, and cell counts at P0, accompanied by increased proliferation (Ki67-positive cells), and elevated apoptosis (CC3-positive) at E16.5, suggesting broader disruptions in progenitor maintenance. Together, these findings suggest Foxr1 is an important regulator of progenitor dynamics and neuron production in cortical and hippocampal development.